Pengaruh Brand Image dan Ulasan Pelanggan Terhadap Minat Beli Smartphone OPPO Di Kota Surabaya - Dwi Prayoga, Ardian; Pudjoprastyono, Hery (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study explores the factors influencing the purchase intention of Oppo smartphones in Surabaya. The factors discussed include brand image and customer reviews. The aim of this research is to determine the impact of brand image and customer reviews on the purchase intention of Oppo smartphones in Surabaya. Data collection in this study was conducted using a questionnaire distribution method and analyzed using the Partial Least Square (PLS) application. The results of this study indicate that brand image and customer reviews have a positive effect on the purchase intention of Oppo smartphones in Surabaya.